Optimization of constructal design of a microchannel heat sink - Abidin, Ummikalsom (2006)
Past studies have shown that a good microchannel design depends on its lower thermal resistance. However, latest theory based on entropy generation minimization (EGM) stated that lower entropy generation rate must also be considered for an optimized microchannel design as is discussed in basic thermodynamics. The present study applies the entropy generation minimization (EGM) method on Li and Peterson’s optimized parallel flow rectangular microchannel. Thermal resistance model, total pressure drop model, and entropy generation rate model are derived to analyze the effects of channel aspect ratio, channel width to channel pitch ratio, heat flux, and pumping power on thermal performance of the microchannel heat sink. The thermal resistance agreed with that of Li and Peterson’s of channel aspect ratio of 6 and a channel number of 120, but the entropy generation rate was not minimized. For the same entropy generation rate value with the same design, an optimum channel number is found to be 60. Only by increasing the channel aspect ratio above 6 gives a minimized entropy generation rate. Therefore, for Li and Peterson’s optimized microchannel design of channel aspect ratio below 6, a minimum entropy generation rate does not exist. Variation of heat flux between 100 and 1000 W/m2 showed no effect on thermal resistance. Lower thermal resistance is obtained with higher overall pumping power at the expense of increasing entropy generation rate. Thus for a parallel microchannel heat sink to be superior in reducing the thermal resistance and in increasing thermodynamics performance, entropy minimization should be taken into account